(Prevalence of Respiratory Symptoms Among Welders in Steel and Air Conditioning Plant (DAMMAM City - Al-Faleh, Dr. Fahad Ali (Arab Journal for Sciences and Research Publishing, 2015)
Aims:  To determine the prevalence of welding related respiratory symptoms. Methods: Cross-sectional study with convenience sampling. The study was conducted among welding workers in air conditioning plant and steel plant in 2014, occupational history questionnaire and respiratory symptoms questionnaire were administered by person-to-person to 110 welders from two plants in DAMMAM city, Saudi Arabia. Results: this study involved 110 welders from two plants, 38 welders from AC plants and 72 welders from steel plants. All welders are male and welding type in AC plant are oxyacetylene welding (oxyacetylene welding (OAW)) and the welding type in steel plant are arc welding. 21 (19.1%) welders from AC plant reported shortness of breath compared to 26 (23.6%) welders from steel plant (Χ2 =2.62, P value =0.03). 16 (42.1%) of welders in AC plant reported cough compared to 24 (33.3%) of welders in steel plant (Χ2 =1.83, P value = 0.03). 20 (52.6%) of welders in AC plant reported phlegm compared to 27 (37.5%) of welders in steel plant (Χ2 =2.33, P value=0.02).  40 (36.4%) of welders reported cough (Χ2 =2.33, P value = 0.04). 47 (42.7%) of welders reported phlegm (Χ2 =3.07, P value = 0.02).  There is no significant associations was founded between (marital status and education level) and respiratory symptoms. Significant association was founded between duration of employment and respiratory symptoms (wheeze (p value=0.03), cough (p value= 0.04), phlegm (p value=0.01). Binary logistic regression was significantly associated between shortness of breath and type of plant (p value=0.01). Conclusion: high prevalence of respiratory symptoms related to type of plant, age of welders and duration of employment. Welders should understand the hazards of the materials they are working with. General ventilation, local exhaust ventilation systems, personal protective equipment are recommended.
Keywords: Prevalence; Respiratory; Symptoms; Welders; Steel; Air Conditioning; Plant